Delta Air Lines, Inc. flying high in a competitive industry an equity research report on Delta Air Lines, Inc. (DAL: NYSE) - Pereira, Pedro Manuel Correia (2020)
This equity research report will first be focusing on the North American Arline industry, analyzing its current form, as well as looking at industry’s opportunities and threats ahead. On top of this, an outlook over the airline industry will also be presented in order to give the investors an accurate view of the present and the future. A further analysis will then be conducted with regards do Delta AirLines Inc. (DAL:NYSE), applying the previous research to provide a fair valuation for the group, resulting in an sustained recommendation of whether an investor should consider invest in DAL, or not.